Cyclic and Macrocyclic Peptides as Chemical Tools To Recognise Protein Surfaces and Probe Protein–Protein Interactions. (13th November 2015) - Cardote, Teresa A. F.; Ciulli, Alessio
Abstract: Targeting protein surfaces and protein–protein interactions (PPIs) with small molecules is a frontier goal of chemical biology and provides attractive therapeutic opportunities in drug discovery. The molecular properties of protein surfaces, including their shallow features and lack of deep binding pockets, pose significant challenges, and as a result have proved difficult to target. Peptides are ideal candidates for this mission due to their ability to closely mimic many structural features of protein interfaces. However, their inherently low intracellular stability and permeability and high in vivo clearance have thus far limited their biological applications. One way to improve these properties is to constrain the secondary structure of linear peptides by cyclisation. Herein we review various classes of cyclic and macrocyclic peptides as chemical probes of protein surfaces and modulators of PPIs. The growing interest in this area and recent advances provide evidence of the potential of developing peptide‐like molecules that specifically target these interactions. Abstract : Can peptides do the job? Peptides can structurally mimic features of protein interfaces, and this makes them attractive candidates to probe and explore sites of protein–protein interactions (PPIs). Improving their stability and physicochemical properties has been the main challenge. This review focuses on cyclic and macrocyclic peptides that aim to address these limitations and how they have been successfully used to target PPIs.